FACTORS ANALYSIS OF FOOTWEAR TRADE INDUSTRY OF INDONESIA MAIN EXPORT DESTINATION - Darwin Simanjuntak (Program Studi Magister Manajemen Universitas Advent Indonesia, 2018)
This study aims to identify the factor that affecting the footwear trade industry in Indonesia based on Indonesia main export destination. Understanding these factors could help leaders in trade industry institutions to better plan their strategies and further research on footwear trading. A set of data was obtained from Badan Pusat Statistic (BPS) based on data from Indonesia footwear main export destination namely: United States, China, Belgium, Germany, Japan, United Kingdom, Netherlands, Korea, Italy, Australia, Mexico, France, Canada, Denmark, Singapore, Brazil, Hong Kong, Russian Federation, Chile, Argentina and Other Countries. Exploratory factor analysis was used to identify the underlying dimensions of countries as Indonesia main export destination. By applying the factor analysis, the study will decide the number of factors to be retained and the total variance explained by these factors; the study can identify the variables in each factor retained in the final solution, on the basis of its factor loadings; the study can give names to each factor retained on the basis of the nature of the variables included in it; the study can suggest the test battery for assessing the footwear trade main export destination in Indonesia; and the study can test the adequacy of sample size used in factor analysis. The result of the study shows that KMO value is 0.784 which is > 0.5; hence, the sample size is adequate for the analysis and the commonalities of all the variables are more than .4; hence, all the variables are useful in the model. Since the variables are identified in factor 0.7 or more, the result shows that all factors which are from the year 2012-2016 contributed to the exports of footwear in Indonesia.